Perils of production with perennial polycultures. (March 2022) - Loomis, Robert S.
Perennial grains and polyculture were proposed ( Renewable Agriculture and Food Systems 20 (1), March 2005) as alternatives to annual grain systems. The authors criticized current annual systems as unsustainable and pointed to native prairies as a model sustainable system with no added input and little negative environmental impact. That portrayal is short-sighted. All previous efforts to breed perennial grains have resulted in crops incapable of supporting both a perennial life-habit and grain yield sufficient to address food needs. Analyses of production/uptake and partitioning of C and N resources within perennial crops confirm that a trade-off between the C and N needs of perennation and grain yield will limit efforts to create productive perennial grains. As a result, incorporating perennial life-habit into grain crops would severely constrain world food production unless the area put to farming was greatly increased. In addition, pest- and risk- management problems, which escalate when sanitizing benefits of crop rotation are abandoned, are exacerbated in polyculture. Although grains contain only small concentrations of nutrients, the amounts exported in crop yields are large. If yield is to be maintained, external inputs are essential, regardless of life-habit. Polycultures of perennial grains are seen to have little potential for producing sufficient food to serve as alternatives for current production systems.